Integrating Sustainable Supply Chain Practices and Risk Management: Strategies to Enhance MSMEs Performance in Indonesia - Annisa Sayyidah Amin; Siti Nursyamsiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to investigate the implementation of Sustainable Supply Chain Management Practices (SSCMP) in Micro, Small, and Medium Enterprises (MSMEs), which are important contributors to economic development but are still limited in their implementation. Through exploring the role of Supply Chain Risk Management (SCRM) as a mediating and moderating variable in improving MSME Sustainable Performance (SP). This study aims to provide a comprehensive understanding of how effective SCRM implementation can significantly affect MSME performance and sustainability. This study adopts a quantitative approach, building on previous studies to formulate hypotheses and conceptual frameworks, and adding a new variable, SCRM. Exploratory Factor Analysis was conducted to align the indicators with the specific conditions of MSMEs in Indonesia. Data were collected from 152 MSMEs in various sectors and processed using SEM-PLS to evaluate the proposed model and test the hypotheses. The findings reveal that SSCMP has a significant positive impact on SP and SCRM. SCRM was found to have a significant positive influence on SP, as well as a significant mediating role in the relationship between SSCMP and SP, thus enhancing the positive impact of SSCMP on performance. Other findings indicate that SCRM does not act as a moderating variable in the relationship between SSCMP and SP, indicating that its influence is more mediating than interactive. This study contributes theoretically by showing that SSCMP positively influences SP and SCRM, with SCRM acting as a significant mediator, but fails to support its role as a moderator in the relationship.